Feasibility, Implementation and Thematic Follow-up in Colombia of the Special Justice for Peace in the Face of the Transitional Justice Structure (2018)
This paper reviews the feasibility, implementation and thematic follow-up of the special justice for peace in opposition to transitional justice in Colombia. The disparity between both ways of conceiving the application of justice in post-conflict processes induces such revision. As an initial method, the non-experimental design allows to review the structure of both forms of justice: later on, complex analysis is applied to address their convergence or disparity. First, the composition of the special justice for peace and the transitional justice are examined. In a second instance, the complexity of both forms of post-conflict justice is characterized. Finally, the feasibility, implementation and thematic follow-up of both are explained in order to show their impacts and results.